Biliary reflux gastritis after Mini Gastric Bypass: The effect of Bilirubin level - Lasheen, Mohamed; Mahfouz, Mohamed; Salama, Tamer; M Salem, Hossam El-Deen (Archives of Surgery and Clinical Research, 2019)
Background: Minigastric bypass is gaining popularity worldwide as an effective bariatric surgery which has fewer complications than RYGB. There is raising concerns about biliary reflux and its effect on gastric mucosa. In this study we tried to find the link between the presence of bile in the stomach and the incidence of gastritis after MGB. Methods: This prospective study was conducted in Ain Shams university hospitals from January 2017 to May 2018 including 40 patients. All patients underwent MGB with a 12-month follow-up, UGI endoscopy was performed 9 months after MGB for all patients, where multiple biopsies and gastric aspirate were obtained for bilirubin level Results: Mean age at operation was 32 years (18–60) and preoperative BMI 44.31 kg/m2. The mean operative time was 95 (± 18 min), Mean % EWL was 81.2% at 12 months. Complete resolution occurred of hypertension in 8 patients (80%) and of Diabetes type 2 in 11 patients (84.2%). Level of bilirubin in gastric aspirate was elevated in 8 patients (20%) all of them had different levels pouch gastritis confirmed by histopathological examination. Conclusion: Biliary reflux reached about 20% after MGB, the severity of biliary gastritis is related to the elevation of bilirubin level in the gastric aspirates, this results need to be confirmed by further studies on the MGB.